2018
DOI: 10.21865/ridep48.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Capital Psicológico de los Trabajadores en España. Análisis Factorial Confirmatorio del PCQ-12

Abstract: ResumenAntecedentes: el concepto de capital psicológico positivo, derivado del estudio del comportamiento organizacional positivo, hace referencia a un estado psicológico caracterizado por autoeficacia, esperanza, resiliencia y optimismo, que puede ser desarrollado y que se relaciona con el rendimiento laboral. Método: este estudio analiza la fiabilidad y estructura factorial del cuestionario de Capital Psicológico (PCQ-12) en una muestra de trabajadores españoles (N=339) de distintos sectores profesionales a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
9
0
2
Order By: Relevance
“…Psychological Capital. We used the shorter Spanish version of the Psychological Capital Questionnaire (PCQ-12) [53] having 12 items. This evaluates four dimensions: Hope (four items; e.g., "Right now I see myself as being pretty successful at work.…”
Section: Instrumentsmentioning
confidence: 99%
“…Psychological Capital. We used the shorter Spanish version of the Psychological Capital Questionnaire (PCQ-12) [53] having 12 items. This evaluates four dimensions: Hope (four items; e.g., "Right now I see myself as being pretty successful at work.…”
Section: Instrumentsmentioning
confidence: 99%
“…The scale was sent to the authors after contacting and requesting authorization through their webpage (www.mindgarden.com) to use its Spanish version. The scale was validated to the Spanish sample by López-Núñez, de Jesús, Viseu, and Santana-Cárdenas [85] in 2017.…”
Section: Psychological Capitalmentioning
confidence: 99%
“…Two studies from Portugal, a country similar to Spain in terms of linguistics and socio-economic context, found that a four-factor model is a better fit than the original model (Rego, Marques, Leal, Sousa, & Pina e Cunha, 2010;Viseu, Jesus, Rus, Nunes, & Lobo, 2012). What is more, two studies of the PCQ12 in Spanish also reveal that the four-factor, rather than the second-order model is the best fit for their data (López-Núñez, de Jesús, Viseu & Santana-Cárdenas, 2017.…”
Section: Psycapmentioning
confidence: 99%
“…Simultaneously, we identified other aspects of the original PCQ12 that can be improved, such as the number of items per dimension. In addition, although there are previous validations in Spanish of the PCQ12 (León-Pérez, Antino, & León-Rubio, 2017, López-Núñez, de Jesús, Viseu & Santana-Cárdenas, 2017there is a lack of validated instruments in Spanish to map PsyCap and its consequences for individuals\ u2019 well-being. Consequently, the goal of this study is to adapt the 12-item short version of the Psychological Capital Questionnaire (PCQ-12, we identified some limitations which the present study aims to overcome.…”
Section: Introductionmentioning
confidence: 99%